Physical Characteristics of Pressed Complete Feed for Dairy Cattle - M. Munasik; C. Imam Sutrisno; Syaiful Anwar; Caribu Hadi Prayitno (Chemical Engineering Diponegoro University, 2013)
The study was aimed to evaluate the physical characteristics of the pressed complete feed in the forms of cube, cylinder and ball. The study was conducted to get a complete feed of dairy cows that can be developed commercially. The evaluation was done on a physical test : bulkiness, hardness and hygroscopic properties of pressed complete feeds. The results of this research showed that the bulkiness of pressed complete feed in the forms cubes, cylinders and balls were between 0.20 up to 0.48 liter/kg; the hardness of pressed complete feed, cylinders and balls were 3 lbs up to 14 lbs; the hygroscopic factor of pressed complete feed in the forms cubes, cylinders and balls were around 1.10% up to 9.69%. The pressed complete feed in the forms of cube and cylinder are better than the form of ball in physical characteristics.doi: 10.12777/ijse.4.2.2013.61-65